European agrifood and forestry education for a sustainable future - Gap analysis from an informatics approach [version 3; peer review: 1 approved, 6 approved with reservations] - Håkan Jönsson; Stephen Burleigh (Open Research Europe)
Background The NextFood Project (www.nextfood-project.eu) started work in 2018 to identify ‘Categories of Skills’ that students should be equipped with to address the upcoming global challenges within agrifood and forestry disciplines. The skill groups are Innovative Mindset, Life-Long Learning, Network-Building, Strategic Management, Sustainability, Systems Perspective, Technological Knowledge and Versatility. This study is based on the initial skills and competencies mapping, but takes a different methodological approach. Instead of investigating what the research literature and professionals think are important skills for the future, this study asks how existing education programmes include or exclude these skills in the description of their programs. Methods Python-based web-scraping scripts were used to collect texts from a selection of European Masters program websites, which were then analysed using statistical tools including Partial Least Squares regression and network analysis. A total of 14 countries, 27 universities, 1303 European Masters programs, 3305 web-pages and almost two million words were studied using this approach. Results While agrifood and forestry Masters programs were aligned with the NextFood Project ‘Categories of Skills’ equal to or more often than unrelated Masters programs, we found evidence for the relative underuse of words associated with networking skills, such as collaboration, communication and eamwork. Agriculture-related programs used these words the least among the agrifood Masters programs. In contrast, agrifood programs used words associated with sustainability and system thinking more than the non-agrifood Masters programs. Conclusions The informatics approach provides evidence that many European agrifood and forestry Masters programs are following the educational paths for meeting future challenges as outlined by the NextFood Project, with the possible exception of networking skills. This approach allows a complementary and time-efficient overview of the current state of education in the agrifood system in Europe.